2021
DOI: 10.1186/s13046-021-01965-z
|View full text |Cite
|
Sign up to set email alerts
|

MYLK4 promotes tumor progression through the activation of epidermal growth factor receptor signaling in osteosarcoma

Abstract: Background Osteosarcoma (OS) is the most common primary bone cancer in adolescents and lung metastasis is the leading cause of death in patients with OS. However, the molecular mechanisms that promote OS growth and metastasis remain unknown. Methods We investigated the expression of myosin light chain kinase family members between metastasis and non-metastasis patients in the TARGET database and ensured that only myosin light chain kinase family me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…MYLK4 encodes a member of the myosin light chain kinase (MYLK) family. MYLKs are involved in the phosphorylation of the myosin light chain and promote the contraction of smooth muscle cells leading to bronchoconstriction [ 34 ]. Although studies on MYLK4 are limited, MYLKs are known to participate in cell migration, invasion, and proliferation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…MYLK4 encodes a member of the myosin light chain kinase (MYLK) family. MYLKs are involved in the phosphorylation of the myosin light chain and promote the contraction of smooth muscle cells leading to bronchoconstriction [ 34 ]. Although studies on MYLK4 are limited, MYLKs are known to participate in cell migration, invasion, and proliferation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…[30] The relationship between osteosarcoma and MYLK is also being unveiled. Yang et al [31] demonstrated through mass spectrometry analysis that MYLK4 interacts with the epidermal growth factor receptor in osteosarcoma cells, promoting growth and metastasis through the epidermal growth factor receptor signaling pathway. Overexpression of MYLK4 accelerates OS growth and metastasis, while silencing MYLK4 expression leads to reduced cell growth and migration.…”
Section: Discussionmentioning
confidence: 99%
“…236,237 Notably, gefitinib (Gef), an efficient EGFR inhibitor, can also repolarize the pulmonary macrophage phenotype by disturbing macrophage receptor-interacting protein kinase 2 (RIPK2) expression to suppress the invasion and metastasis of osteosarcoma. [238][239][240] Additionally, Gef can also relieve postoperation-accelerated osteosarcoma metastasis and prolong overall survival time in a mouse model of osteosarcoma. 241 Various compounds have also been derived from natural products, including epimedokoreanin B (derived from Epimedii Herba), 242 onion A1 (derived from allium sulfides), 243 and oleanolic acid (OA)/corosolic acid (CA).…”
Section: Conventional Immunotherapy For Osteosarcomamentioning
confidence: 99%